Pengembangan LKPD Berbasis Budaya Melayu dengan Model Problem Based Learning Berbantuan Canva - Lubis, Nur Azura; Saragih, Risna Mira Bella; Matondang, Khoiruddin (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This research aims to produce a valid, practical, and effective Malay culture-based Student Worksheet (LKPD) on the set theory material for seventh-grade students. The study uses the 4-D Research and Development (R&D) model. The subjects of this research were 32 students from the seventh grade of SMP Negeri 3 Tanjung Beringin. The analysis of the LKPD scores by the validators resulted in an index of 0.96 from the material expert, categorized as high or very valid, an index score of 0.96 from the media expert, also categorized as high or very valid, and an index score of 0.93 from the language expert, categorized as high or valid. The teacher's questionnaire classification met the criteria of "very good" with an average score of 4.8 out of a maximum score of 5.00. The student questionnaire results met the criteria of "strong" or practical with a percentage of 86.09%, indicating that the Malay culture-based LKPD has practical quality. The effectiveness was obtained from the N-gain calculation, with an average of 0.77, categorized as high, showing that the Malay culture-based LKPD is effective in improving student learning outcomes.